2000
DOI: 10.1088/0029-5515/40/3y/312
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of tritium accountancy technology for ITER fuel cycle safety enhancement

Abstract: In order to improve the safe handling and control of tritium for ITER fuel cycle, effective "in-situ" tritium accounting methods have been developed at Tritium Process Laboratory in Japan Atomic Energy Research Institute under one of the ITER-EDA R&D Tasks. A remote and multi-location analysis of process gases by an application of laser Raman spectroscopy developed and tested could provide a measurement of hydrogen isotope gases with a detection limit of 0.3 kPa for 120 seconds analytical periods. An "in-situ"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…On the other hand, there are two beds for 25 g and 10 g of tritium storage, with "in-bed" gas flowing calorimetric function for self-accountancy, as reported in Refs. [11][12][13]. Each capacity is based on ZrCoQ 1.8 (Q = H,D,T).…”
Section: Typical Design Of a Zrco Tritium Storage Bedmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there are two beds for 25 g and 10 g of tritium storage, with "in-bed" gas flowing calorimetric function for self-accountancy, as reported in Refs. [11][12][13]. Each capacity is based on ZrCoQ 1.8 (Q = H,D,T).…”
Section: Typical Design Of a Zrco Tritium Storage Bedmentioning
confidence: 99%
“…However, it also has disadvantages from the safety point of view, such as high pyrophoricity with oxygen, high reactivity with nitrogen, fine powdering, etc., and it is a controlled nuclear material in Japan, even if it is depleted. On the other hand, zirconium-cobalt (ZrCo), an inter-metallic compound, has been investigated and demonstrated as a tritium storage material instead of U at the Tritium Process Laboratory (TPL) of the Japan Atomic Energy Agency (JAEA) for about 20 years [9][10][11][12][13][14] and at the Tritium Laboratory Karlsruhe of the FzK [15][16][17][18]. ZrCo has many attractive characteristics from the safety point of view, such as low reactivity with oxygen and nitrogen, similar equilibrium pressure isotherm, and it is not a nuclear material, so it can be handled everywhere.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note and relevance to the work described in our present paper is the fibre-coupled tritium accounting system developed by O'hira et al [13], which aimed at improving the safe handling and control of tritium for the fuel cycle of the ITER tokomak fusion reaction concept. This system demonstrated that the isotopomeric composition of a tritium gas flow under high flow (up to 200 Pa m 3 s…”
Section: Introductionmentioning
confidence: 97%
“…For example, KATRIN successfully employs Raman spectroscopy monitoring for continuous, in-line compositional analysis of its circulating source gas [ 7 ]. For the accountancy of tritium in the fusion fuel cycle of ITER/DEMO, Raman spectroscopy has been evaluated as one possible analytical tool [ 8 , 9 , 10 ], which is still partially under procurement [ 11 ], or is under development but has not been tested with tritium yet [ 12 ].…”
Section: Introductionmentioning
confidence: 99%